👤

Show your solutions.
Transform y = 3x2 - 4x + 1 into the form y = a(x - h)? + k.​


Sagot :

Transform y = 3x² - 4x + 1 into the form y = a(x - h) + k

[tex]\[\begin{array}{l}y = 3{x^2} - 4x + 1\\\\y = 3({x^2} - \frac{4}{3}x) + 1\\\\y = 3(({x^2} - \frac{4}{3}x + {(\frac{2}{3})^2}) + 1 - 3{(\frac{2}{3})^2}\\\\y = 3(({x^2} - \frac{4}{3}x + {(\frac{2}{3})^2}) + 1 - 3(\frac{4}{9})\\\\y = 3{(x - \frac{2}{3})^2} - \frac{1}{3}\end{array}\][/tex]

Answer:

[tex]\[y = 3{(x - \frac{2}{3})^2} - \frac{1}{3}\][/tex]

#CarryOnLearning